The impact of surgical menopause on metabolic syndrome, bone mineral density, and vasomotor symptoms - ANIK İLHAN, GÖKÇE (IMR PRESS, 2020)
Purpose: The aim of this study is to compare the effects of surgical and natural menopause on vasomotor symptoms, osteoporosis, and metabolic syndrome. Materials and Methods: Seventy menopausal women fulfilling the inclusion criteria were divided into two groups according to surgical and natural menopause. Metabolic syndrome (MS) was defined according to the International Diabetes Federation. Vasomotor symptoms were scored according to the presence of hot flashes and night sweats. The participants had a bone mineral density (BMD) evaluation of the total lumbar spine and total hip bone. Results: The rates of vasomotor symptoms were similar among groups (p > 0.05). MS was significantly higher in surgical menopause group than in natural menopause group (p < 0.05). Women with surgical menopause were found to be more osteopenic at level L1-L4 (p < 0.05). Furthermore there were no differences between the femoral neck, femora total T scores, and BMDs of two groups. Conclusion: Compared with natural menopause, surgical menopause was found to be associated with higher rates of MS and osteoporosis but not with vasomotor symptoms.
Keywords: Surgical and natural menopause; Vasomotor symptoms; Bone mineral density; Metabolic syndrome; RISK; OOPHORECTOMY; POPULATION; AGE; LIPOPROTEINS; ADIPOSITY; LIPIDS; WOMEN